Psychologists’ Experiences Conducting Suicide Risk Assessments: A Phenomenological Study - Dubue, Jonathan D.; Hanson, William E. (Canadian Journal of Counselling and Psychotherapy, 2020)
Psychologists conduct suicide risk assessments (SRAs) regularly to identify and prevent clients’ self-harm and risk of death, although little is known about their experiences of the process. In this phenomenological study, five registered psychologists (master’s and doctoral level) were interviewed to explore the essence of their SRA experiences. Psychologists reported weaving tenets of assessment and therapy throughout their SRAs, relying on their clinical intuition, and investing deeply in their suicidal clients. Also, psychologists reported feeling significant anxiety working with suicidal clients, revealing the ways in which the fear of client suicide guides and motivates their SRA practices. While they have an empathic view of suicide, they believe in preventative intervention. They reported feeling pressure from clients and colleagues to conduct ethical and useful SRAs despite receiving what they consider to be insufficient and ineffectual graduate SRA training. Results from this study offer a qualitative foundation for future research on the ethics, training, and practice of SRA.